The Impacts of Biotechnology on Biodiversity in Global Health: A Case Study on Avian Influenza in Bangladesh - Muhiuddin Haider; Milind Patel; Priyanka Bhattacharjee; Maariya Bassa (International Journal of Public Health Science (IJPHS), 2015)
Biodiversity is the variability of between genetics, species, or ecosystems of living organisms within a specific region. Biodiversity is essential for sustaining healthy living networks and systems because it allows for a variety of food sources, medicine, and biological control, while also playing a significant role in atmospheric regulation, nutrient cycling, and pollination. Loss of biodiversity and ecosystem change increases the risk of the emergence or spreading of infectious diseases and global pandemics such as the Avian Influenza (AI H5N1). Biotechnology is one solution for reducing, and ultimately eliminating, the transmission of avian influenza. Traditional methods of treating infected animals, such as common vaccines, are temporary solutions that have no effect on the biodiversity of an ecosystem. Methods in animal biotechnology such as artificial insemination, embryo transfer, and in vitro fertilization have led to developments of cheaper, safer, and more effective vaccines. Livestock that have been treated for H5N1, as well as those that are healthy and have never been infected have proven to increase the diversity, leading to the elimination of specific issues. Similar effects are attainable if these animal biotechnology methods were to be used on poultry infected with the avian influenza virus.